2013
DOI: 10.1016/s0022-3913(13)60374-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preparation design and ceramic thicknesses on fracture resistance and failure modes of premolar partial coverage restorations

Abstract: Statement of problem Preparation designs and ceramic thicknesses are key factors for the long-term success of minimally invasive premolar partial coverage restorations. However, only limited information is presently available on this topic. Purpose The aim of this in vitro study was to evaluate the fracture resistance and failure modes of ceramic premolar partial coverage restorations with different preparation designs and ceramic thicknesses. Material and methods Caries-free human premolars (n= 144) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 47 publications
6
125
4
5
Order By: Relevance
“…This reproduction of the in vivo condition was designed to observe changes representative of the expected clinical in vivo changes, which might result in the undesired phenomenon of low temperature degradation (LTD) 20) . In the study, a load application in the range of physiologic occlusal forces of 50 N was selected according to previous studies 17,29) . All FDPs survived the artificial aging in the chewing simulator, indictating this result a stable performance of the zirconia ceramics analyzed in the presence of mechanical and thermal stress like in the oral environment, as previously reported 17,20,29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reproduction of the in vivo condition was designed to observe changes representative of the expected clinical in vivo changes, which might result in the undesired phenomenon of low temperature degradation (LTD) 20) . In the study, a load application in the range of physiologic occlusal forces of 50 N was selected according to previous studies 17,29) . All FDPs survived the artificial aging in the chewing simulator, indictating this result a stable performance of the zirconia ceramics analyzed in the presence of mechanical and thermal stress like in the oral environment, as previously reported 17,20,29) .…”
Section: Discussionmentioning
confidence: 99%
“…In the study, a load application in the range of physiologic occlusal forces of 50 N was selected according to previous studies 17,29) . All FDPs survived the artificial aging in the chewing simulator, indictating this result a stable performance of the zirconia ceramics analyzed in the presence of mechanical and thermal stress like in the oral environment, as previously reported 17,20,29) . In the study 3-point flexure test until fracture was used as previously reported 4,18) .…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors influencing the fracture resistance of ceramic restorations 5,[8][9][10] . The fracture resistance of all-ceramic restorations can be increased by an ideal combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The material characteristics of ceramics have been shown to significantly depend on prior thermal and mechanical fatigue loading 4) . Four factors have been identified to mainly influence the fracture resistance of all-ceramic restorations: restoration design, tooth preparation, cementation and material thickness [5][6][7][8][9] . The fracture resistance can be increased by an ideal combination of these four factors, however, the factors restoration material and material thickness have been reported to be of primary importance 10) .…”
Section: Introductionmentioning
confidence: 99%
“…The restoration geometry, design considerations, preparation methods, and loading conditions are key factors for the long-term success of dental restorations [2][3][4][5][6][7][8]. For tooth-colored ceramic inlays in esthetic dentistry, the long-term success is an actual problem [7].…”
Section: Introductionmentioning
confidence: 99%